Fabrication and characterization of 3D‐printed elastic auricular scaffolds: A pilot study. (19th September 2018) - Kim, Ha Yeong; Jung, Soo Yeon; Lee, Sang Jin; Lee, Hyun Jung; Truong, Minh‐Dung; Kim, Han Su
Abstract : Objective: Aesthetic reconstruction of the external ear is challenging due to the complex anatomical shape of the auricle. Recently, artificial scaffolds such as Medpor (Stryker, Kalamasoo, MI, USA) have become widely used in ear reconstruction. However, the Medpor scaffold is stiffer than the natural ear, which may lead to discomfort, and moreover has uniform design for every patient. In this study, we investigated whether three‐dimensional (3D)‐printed artificial polyurethane (PU) scaffolds are suitable for auricular reconstruction. Methods: PU scaffolds were fabricated using 3D printing according to a design derived from a digital imaging and communications in medicine (DICOM) image of the human auricle. The microstructure of the scaffolds was observed using scanning electron microscopy, and the porosity was examined. Cell proliferation on the scaffolds was assessed in vitro using tonsil‐derived mesenchymal stem cells to evaluate the biocompatibility of the scaffolds. The scaffolds were implanted in C57BL/6 mice, and histological analysis was performed. Results: The structural study revealed that the 3D‐printed porous PU scaffolds have rectangular microstructure with regular pitch and line, as well as high porosity (56.46% ± 10.22%) with a pore diameter of 200 µm. The mechanical properties of the 3D‐printed PU scaffolds were similar to those of the human auricle cartilage. Cell proliferation on the PU scaffolds was greater than that on Medpor scaffolds. Histological evaluation demonstrated that the porous parts of the PU scaffolds became filled with collagen and vascular tissue. Conclusion: Elastic, porous PU scaffolds can be obtained using 3D printing, have biomechanical properties similar to those of the natural ear, and are suitable for use in auricular reconstruction. Level of Evidence: NA Laryngoscope, 129:351–357, 2019